The influence of growth, maturation and resistance training on muscle-tendon and neuromuscular adaptations: a narrative review - Tumkur Anil Kumar, N.; Oliver, J. L.; Lloyd, R. S.; Pedley, J. S.; Radnor, J. M. (Sports, 2021)
The purpose of this article is to provide an overview of the growth, maturation and resistance training-related changes in muscle-tendon and neuromuscular mechanisms in youth, and the subsequent effect on performance. Sprinting, jumping, kicking, and throwing are common movements in sport that have been shown to develop naturally with age, with improvements in performance being attributed to growth and maturity-related changes in neuromuscular mechanisms. These changes include moderate to very large increases in muscle physiological cross-sectional area (CSA), muscle volume and thickness, tendon CSA and stiffness, fascicle length, muscle activation, pre-activation, stretch reflex control accompanied by large reductions in electro-mechanical delay and co-contraction. Furthermore, a limited number of training studies examining neuromuscular changes following four to 20 weeks of resistance training have reported trivial to moderate differences in tendon stiffness, muscle CSA, muscle thickness, and motor unit activation accompanied by reductions in electromechanical delay (EMD) in pre-pubertal children. However, the interaction of maturity- and training-related neuromuscular adaptions remains unclear. An understanding of how different neuromuscular mechanisms adapt in response to growth, maturation and training is important in order to optimise training responsiveness in youth populations. Additionally, the impact that these muscle-tendon and neuromuscular changes have on force producing capabilities underpinning performance is unclear.